A Developmental Sequence Model to University Adjustment of International Undergraduate Students - Chavoshi, Saeid; Wintre, Maxine Gallander; Dentakos, Stella; Wright, Lorna (Journal of International Students, 2018)
The current study proposes a Developmental Sequence Model to University Adjustment and uses a multifaceted measure, including academic, social and psychological adjustment, to examine factors predictive of undergraduate international student adjustment. A hierarchic regression model is carried out on the Student Adaptation to College Questionnaire to examine theoretically pertinent predictors arranged in a developmental sequence in determining adjustment outcomes. This model accounted for over 60% of the variance in adjustment scores, and highlighted the importance of ecological factors in relation to student adjustment, such as social support, relationship with parents, and perceived institutional support as more useful than static measures of achievement such as high school GPA. Implications of these findings, including the important role of campus services, are discussed.